Digital Media Habit dan Pemahaman Politik Elektoral Calon First Voters Wilayah Perkotaan - Sujana, Komang Hanita Ayu Arisanthi; Pramana, Gede Indra; Apriani, Kadek Dwita (Jurnal Nawala Politika, 2023)
This research seeks to explain behavior patterns of first-time voters using media as a source of information to increase their awareness about elections in urban areas. Generations, New Media, and Uses & Gratification Theory were applied for the research. A descriptive quantitative is an appropriate method for this research. For sampling technique used is simple random sampling and data were acquired by disseminating questionnaires. Denpasar is a suitable city for this research because Denpasar was the provincial capital of Bali with the highest internet penetration rate. This research tries to see how Generation Z in urban areas uses the internet in various aspects, including elections. The results appear that technology is a common thing for Generation Z in Denpasar city, they choose the internet as a trusted medium for finding and learning about elections and politics at both regional and national. This research also showed that the apathy assumption was refused because first-time voter Denpasar had an interest in political participation